EFEK ANTIBAKTERI EKSTRAK BUAH MAHKOTA DEWA TERHADAP Enterococcus faecalis SEBAGAI MEDIKAMEN SALURAN AKAR: ANTIBACTERIAL EFFECT OF EXTRACT MAHKOTA DEWA'S FRUIT TO Enterococcus faecalis AS ROOT CANAL MEDICAMENT - Darwis Aswal; Lusiana Beatrice (TALENTA, 2010)
Mahkota dewa’s fruit or Phaleria macrocarpa.Scheff (Boerl) had been choosen as an alternative root canal medicamentsolution because the low saponin that obtained on fruit and other compound such as alcaloid and tannin which act as anantibacteria. Enterococcus faecalis is one of the resistance bacteri and found in endodontic infections. The existence ofthis bacteria is able to make colonization or a good adherence on the protein surface and to form biofilm in dentinal walls.This study was aimed to know the antibacterial effect of extract mahkota dewa’s fruit by knowing the low concentrationto inhibit and kill E. faecalis. It was begun with extraction 800 grams mahkota dewa’s fruit, then had been macerated with5 liters of etanol 96% became 2.5 liters of macerat liquid. The macerat had been evaporated with Vaccum RotaryEvaporator and resulted extract viscous consistency mahkota dewa’s fruit. To find the antibacterial effort of this fruit wasdetermined by minimum inhibitory concentration and minimum bactericidal concentration with the concentration of100%, 50%, 25%, 12,5% and 6,25%. The conclusion of this study was 12,5% extract mahkota dewa’s fruit with the score0 CFU/ml can be developed as an alternative root canal medicament solution.